تنمية القدرات السياحية السورية (كمدخل لتطوير هذا القطاع) - قنوع, نزار; عباس, لورا (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتضمن هذا البحث دراسة لأوضاع قطاع السياحة في الدول العربية في ضوء المؤشرات والمعايير الدولية والإقليمية. هذه المؤشرات التي تدل على أنه وبالرغم من هيمنة الدول الصناعية المتقدمة في هذا المجال، فإن الدول الفقيرة والنامية لديها من الإمكانات ما يؤهلها لكي تكون رائدة في إقامة صناعة سياحية متطورة، كما ويتضمن هذا البحث الإشارة إلى أهمية الاستثمار السياحي في سورية من خلال دراسة مقارنة مع بعض الدول. ويسلط الضوء على مقومات النمو السياحي وتنمية القدرة التنافسية السياحية السورية في إطار استراتيجية الصناعة الوطنية. This paper contains a study of the situations of the tourism sector in Arab countries in the light of international and regional indexes and criterions. These indexes indicate that in spite of the domination of the advanced industrial countries in this field, the poor and developing countries have such abilities that qualify them to be pioneers in the creation of developed tourism industries; also this paper includes reference to the importance of tourist investment in Syria through a comparative study with some countries. And it highlights the constituents of the tourist development and growing the competitive ability of Syrian tourism in the frame of the strategy of national industry.